A primer for studying cell cycle dynamics of the human hair follicle. Issue 9 (18th July 2016) - Purba, Talveen S.; Brunken, Lars; Hawkshaw, Nathan J.; Peake, Michael; Hardman, Jonathan; Paus, Ralf
Abstract: The cell cycle is of major importance to human hair follicle (HF) biology. Not only is continuously active cell cycling required to facilitate healthy hair growth in anagen VI HFs, but perturbations in the cell cycle are likely to be of significance in HF pathology (i.e. in scarring, non‐scarring, chemotherapy‐induced and androgenic alopecias). However, cell cycle dynamics of the human hair follicle (HF) are poorly understood in contrast to what is known in mouse. The current Methods Review aims at helping to close this gap by presenting a primer that introduces immunohistological/immunofluorescent techniques to study the cell cycle in the human HF. Moreover, this primer encourages the exploitation of the human HF as a powerful and clinically relevant tool to investigate mammalian cell cycle biology in situ . To achieve this, we describe methods to study markers of general 'proliferation' (nuclei count, Ki‐67 expression), apoptosis (terminal deoxynucleotidyl transferase dUTP nick‐end labelling, cleaved caspase 3), mitosis (phospho‐histone H3, 'pS780'), DNA synthesis (5‐ethynyl‐2′‐deoxyuridine) and cell cycle regulation (cyclins) in the human HF. In addition, we provide specific examples of dual immunolabelling for instructive cell cycle analyses and for investigating the cell cycle behaviour of specific HF keratinocyte subpopulations, such as keratin 15+ stem/progenitor cells.